Incidence and predictors of diabetic kidney disease among type 2 diabetes mellitus adult patients in Ethiopia: a systematic review and meta-analysis - Muluken Amare Wudu; Tarikua Afework Birhanu; Kirubel Dagnaw Tegegne; Endalk Birrie Wondifraw (BMC Endocrine Disorders)
Abstract Background Diabetic kidney disease is a leading cause of end-stage renal disease and mortality among patients with type 2 diabetes mellitus worldwide. Currently, there are no pooled estimates of the incidence of diabetic kidney disease or its modifiable predictors among patients with type 2 diabetes mellitus in Ethiopia. Therefore, this review aimed to determine the pooled incidence and associated factors of diabetic kidney disease in Ethiopia, addressing the existing information gap. Methods Relevant studies were retrieved from PubMed, Scopus, EMBASE, and Google Scholar. Four reviewers independently screened studies, and data were extracted using a structured form. Quality assessment was conducted using the Joanna Briggs Institute critical appraisal checklist. Data analysis was performed in STATA version 17 using the Šidák–Jonkman random-effects model. Heterogeneity was evaluated using Cochrane’s Q-test and the I² statistic, while publication bias was assessed using funnel plots, Egger’s test, and a Doi plot. Results Of the 165,230 studies identified, eight studies involving 3,703 participants were included in the meta-analysis. The pooled incidence of diabetic kidney disease among patients with type 2 diabetes mellitus was 2.37 per 100 person-years (95% CI: 1.76–2.97; I² = 99.85%), based on 29,916.35 person-years of observation. Moreover, study setting and follow-up period (R²=83.21%) were considered as the source of heterogeneity. Furthermore, the pooled median time to develop diabetic kidney disease was 101.38 months (95% CI: 72.79–129.97). Factors associated with diabetic kidney disease included older age (> 60 years) (HR: 1.02, 95% CI: 1.01–1.03), hypertension (HR: 2.07, 95% CI: 1.83–2.34), cardiovascular disease (HR: 1.53, 95% CI: 1.29–1.81), and low high-density lipoprotein cholesterol (HDL-C) levels (< 40 mg/dL) (HR: 1.70, 95% CI: 1.42–2.05). Conclusion The incidence of diabetic kidney disease in this review was high, highlighting the need for intensified efforts to achieve the 2030 kidney health target and improve patients’ quality of life. Moreover, older age, hypertension, cardiovascular disease, and low HDL-C levels were identified as risk indicators of diabetic kidney disease. This suggests strengthening early routine risk-based screening, especially in older adults, and implementing intensive management of hypertension, cardiovascular disease, and dyslipidemia to address the identified factors.